Website Management Training and ICT Literacy Evaluation of Kelurahan Ciwaringin Bogor Authorities - Halimah Tus Sadiah (International Journal of Quantitative Research and Modeling, 2020)
The use and management of e-Government websites as a mean of public service among Kelurahan Ciwaringin Bogor (Ciwaringin Bogor Village) officials are still considered low. This has implications on the level of online public services in Ciwaringin Bogor Village which is less optimal. This research aims to provide website management training and to conduct an evaluation on information and communications technology (ICT) literacy prior to (plan) and after (reflect) the training of Ciwaringin Bogor Village authorities in order to optimize the usage of e-Government website for public service improvement purpose. The research method consists of three stages, namely: Planning, Website Management Training, and Reflecting. The training is conducted 10 times from February 2019 to April 2019. Based on evaluation of the planning and reflecting stages, the authorities are ready for ICT usage and management as there is a significant improvement in e-Government website management skill of the Ciwaringin Bogor Village authorities from 40% to 80%.